1980
DOI: 10.1113/jphysiol.1980.sp013431
|View full text |Cite
|
Sign up to set email alerts
|

Chromaffin cell action potentials and their possible role in adrenaline secretion from rat adrenal medulla.

Abstract: SUMMARY1. The role of action potentials in adrenaline secretion was investigated in the rat adrenal medulla. The effects of various treatments on adrenaline secretion from the perfused adrenal medulla were compared with the effects of similar treatments on spike frequency in dissociated adrenal chromaffin cells.2. KCl concentrations between 10 and 20 mm increased the extracellularly recorded spike frequency of dissociated adrenal chromaffin cells. Upon perfusion by a KCl concentration of 30 mM there was an ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
2

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(122 citation statements)
references
References 33 publications
(73 reference statements)
8
112
2
Order By: Relevance
“…Under low frequency APe stimulation matching splanchnic firing under basal sympathetic tone (0.5 Hz) [39][40][41], we show that transfection with a peptide fragment of the Dynamin I prolinerich domain (PRD) that competitively competes for binding to amphiphysin [17] has the result of blocking granule endocytosis. Consistent with previous work [4,19,25], disrupting clathrinmediated endocytosis by blocking synaptojanin/endophilin binding has no effect on membrane retrieval in these conditions.…”
Section: Discussionmentioning
confidence: 94%
“…Under low frequency APe stimulation matching splanchnic firing under basal sympathetic tone (0.5 Hz) [39][40][41], we show that transfection with a peptide fragment of the Dynamin I prolinerich domain (PRD) that competitively competes for binding to amphiphysin [17] has the result of blocking granule endocytosis. Consistent with previous work [4,19,25], disrupting clathrinmediated endocytosis by blocking synaptojanin/endophilin binding has no effect on membrane retrieval in these conditions.…”
Section: Discussionmentioning
confidence: 94%
“…An electrophysiological study demonstrated the presence of several types of K+ channels in chromaffin cells and its inhibition by TEA (Marty & Neher, 1985). Further, Kidokoro & Ritchie (1980) explained the stimulatory action of TEA on KCI-induced CA secretion with regard to the action potential, and suggested that TEA is only effective on the portion of CA secretion which is mediated by spike activity. The present study demonstrated that the enhancement by TEA of GABA-evoked CA secretion was inhibited by TTX and removal of extracellular Na+.…”
Section: [Ca2 +]Imentioning
confidence: 99%
“…We used amperometry to quantify the kinetics of catecholamine release from cells stimulated with APe voltage templates delivered at 0.5 or 15 Hz in perforated-patch voltage clamp. These conditions mimic splanchnic input under sympathetic tone or acute stress, respectively (Kidokoro and Ritchie, 1980;Chan and Smith, 2001;Wilson et al, 2002).…”
Section: Disrupting the Actin Cortex Increases Amperometric Spike Ampmentioning
confidence: 99%
“…This exocytic mode is characterized by transient fusion of the granule with the cell membrane, maintenance of basic granule morphology, and retention of the dense proteinaceous granule core (Fulop et al, 2005). In contrast, under acute stress, increased splanchnic firing and subsequent acetylcholine release drive chromaffin cells to increase their activity level (Brandt et al, 1976;Kidokoro and Ritchie, 1980), resulting in elevated catecholamine output. Under these conditions, the restricted fusion pore dilates, leading to a full granule collapse and expulsion of both catecholamine and the neuropeptide-containing proteinaceous core (Rahamimoff and Fernandez, 1997;Fulop et al, 2005).…”
Section: Introductionmentioning
confidence: 99%